Nonlinear Optical Switching in Regioregular Porphyrin Covalent Organic Frameworks - Biswal, Bishnu P.; Valligatla, Sreeramulu; Wang, Mingchao; Banerjee, Tanmay; Saad, Nabil A.; Mariserla, Bala Murali Krishna; Chandrasekhar, Naisa; Becker, Daniel; Addicoat, Matthew; Senkovska, Irena; Berger, Reinhard; Rao, D. Narayana; et al. (Angewandte Chemie International Edition, 2019)
Covalent organic frameworks (COFs) have garnered immense scientific interest among porous materials because of their structural tunability and diverse properties. However, the response of such materials toward laser-induced nonlinear optical (NLO) applications is hardly understood and demands prompt attention. Three novel regioregular porphyrin (Por)-based porous COFs—Por-COF-HH and its dual metalated congeners Por-COF-ZnCu and Por-COF-ZnNi—have been prepared and present excellent NLO properties. Notably, intensity-dependent NLO switching behavior was observed for these Por-COFs, which is highly desirable for optical switching and optical limiting devices. Moreover, the efficient π-conjugation and charge-transfer transition in ZnCu-Por-COF enabled a high nonlinear absorption coefficient (β=4470 cm/GW) and figure of merit (FOM=σ1/σo, 3565) value compared to other state-of-the-art materials, including molecular porphyrins (β≈100–400 cm/GW), metal–organic frameworks (MOFs; β≈0.3–0.5 cm/GW), and graphene (β=900 cm/GW).
CRIS-Team Scopus Importer:2022-04-14
Keywords: covalent organic frameworks; microporous materials; nonlinear optics; porphyrins; regioregular materials